Evaluation of the digestible lysine requirements in female turkeys from 0 to 68 days of age - Paula Dorigam, Juliano Cesar de [UNESP]; Appelt, Matias Djalma; Maiorka, Alex; Muramatsu, Keysuke; Sens, Rafael Fernando; Rocha, Chayane; Dahlke, Fabiano (Elsevier B.V., 2016)
Over the past years, turkey meat has gained a prominent position in the global market. As lysine (Lys) is among the main essential amino acids (AA) for protein deposition in the carcass, defining Lys requirements can contribute to improving the performance and carcass yield of turkey for meat production. Thus, the objective of this study was to evaluate if the digestible Lys levels proposed by breeder's guidelines are adequate to achieve the best performance in the used rearing and feed conditions of this study. In each phase, 800 female turkeys of the BUT (British United Turkey) hybrid strain were used. The turkeys were distributed in a completely randomized design in experiment 1 (initial phase: 0-25 d) and in a randomized block design in experiment 2 (growth phase: 26-48 d) and experiment 3 (finishing phase: 49-68 d). The treatments consisted of graded levels of digestible Lys with eight replications of 20 turkeys each. The digestible Lys levels tested were 13.6, 14.5, 15.8, 16.9 and 18.2 g/kg in the initial phase; 12.2, 13.2, 14.4, 15.4 and 16.2 g/kg in the growth phase; and 9.7, 10.4, 11.4, 12.1 and 13.7 g/kg in the finishing phase. The average daily gain (ADG), average daily feed intake (ADFI), feed efficiency (FE) and carcass yield (CY) were evaluated. The ADG, FE and CY data were improved by the digestible Lys levels (P<0.05), and the data were adjusted to the quadratic and broken line functions. The digestible Lys level was estimated by the first intercept of the quadratic function with the plateau of the broken line function. At the end of experiment 3, the CY was evaluated (at 68 d). The digestible Lys level for better ADG and FE were, respectively, 16.69 g/kg and 16.55 g/kg in the initial phase, 14.25 g/kg and 14.15 g/kg in the growth phase, and 12.23 g/kg and 12.07 g/kg in the finishing phase. The digestible Lys level for CY was 12.32 g/kg. The current study concludes that digestible Lys levels are in the range of the nutritional guidelines for the strain used, except in the initial phase. Due to the difference in the initial recommendation, these levels should be validated in further investigations through performance trials. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amino acid; Broken line; Carcass yield; Female turkey; Quadratic polynomial